Interleukin-22 in Graft-Versus-Host Disease after Allogeneic Stem Cell Transplantation - Lamarthée, Baptiste; Malard, Florent; Saas, Philippe; Mohty, Mohamad; Gaugler, Béatrice (Frontiers in Immunology, 2016)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potential curative treatment for hematologic malignancies as well as non-malignant diseases. Because of the lower toxicity of reduced intensity conditioning, the number of transplants is in constant increase. However, allo-HSCT is still limited by complications, such as graft-versus-host-disease (GVHD), which is associated with important morbidity and mortality. Acute GVHD is an exacerbated inflammatory response that leads to the destruction of host healthy tissues by donor immune cells. Recently, the contribution of innate immunity in GVHD triggering has been investigated by several groups, and resulted in the identification of new cellular and molecular effectors involved in GVHD pathogenesis. Interleukin-22 (IL-22) is produced by both immune and adaptive cells, and has both protective and inflammatory properties. Its role in GVHD processes has been investigated, and the data suggest that its effect depends on the timing, the target tissue and the origin of the producing cells (donor/host). In this review, we discuss the role of IL-22 in allo-HSCT and GVHD.